Analysis on Differential Router Buffer Size towards Network Congestion: A Simulation-based - Nahar, H.; Muslim, Z.; Shibghatullah, A. S.; Sahib, S. (IJCSIS Managing Editor, 2011)
Network resources are shared amongst a large number of users. Improper managing network traffic leads to congestion problem that degrades a network performance. It happens when the traffic exceeds the network capacity. In this research, we plan to observe the value of buffer size that contributes to network congestion. A simulation study by using OPNET Modeler 14.5 is conducted to achieve the purpose. A simple dumb-bell topology is used to observe several parameter such as number of packet dropped, retransmission count, end-to-end TCP delay, queuing delay and link utilization. The results show that the determination of buffer size based on Bandwidth-Delay Product (BDP) is still applicable for up to 500 users before network start to be congested. The symptom of near-congestion situation also being discussed corresponds to simulation results. Therefore, the buffer size needs to be determined to optimize the network performance based on our network topology. In future, the extension study will be carried out to investigate the effect of other buffer size models such as Stanford Model and Tiny Buffer Model. In addition, the buffer size has to be determined for wireless environment later on.